2019
DOI: 10.1111/tid.13081
|View full text |Cite
|
Sign up to set email alerts
|

A case of Pneumocystis pneumonia, with a granulomatous response and vitamin D‐mediated hypercalcemia, presenting 13 years after renal transplantation

Abstract: Vitamin D‐mediated hypercalcemia is an uncommon complication of Pneumocystis infection. A granulomatous response resulting from Pneumocystis infection is also atypical. In this report, we describe an exceptional case of granulomatous Pneumocystis pneumonia associated with vitamin D‐mediated hypercalcemia, in a patient who presented unusually late after renal transplantation. The patient's hypercalcemia resolved with treatment of the infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…According to a study of PCP cases among kidney transplant recipients, hypercalcemia was observed in 37% of PCP patients with high 1,25-(OH) 2 vitamin D and low parathyroid hormone (PTH), suggesting a granuloma-mediated mechanism [ 30 ]. This resolved after successful treatment of PCP pneumonia [ 31 ]. Hypercalcemia has also been reported in patients with PCP infection who have undergone liver transplant or have AIDS [ 32 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to a study of PCP cases among kidney transplant recipients, hypercalcemia was observed in 37% of PCP patients with high 1,25-(OH) 2 vitamin D and low parathyroid hormone (PTH), suggesting a granuloma-mediated mechanism [ 30 ]. This resolved after successful treatment of PCP pneumonia [ 31 ]. Hypercalcemia has also been reported in patients with PCP infection who have undergone liver transplant or have AIDS [ 32 33 ].…”
Section: Discussionmentioning
confidence: 99%